Penerapan Model Rehabilitasi Bagi Pecandu Narkotika - Ana Ilmadan Sari; Selpa Rosalenda; Olivia Sugiarti; Asep Suherman (GLOBAL SCIENTS PUBLISHER, 2026)
Drug abuse by addicts is a complex legal and social issue because it relates not only to criminal aspects but also to health and human rights. However, in Indonesian law enforcement practices, drug addicts are still often positioned as criminals sentenced to imprisonment, rather than as victims requiring rehabilitation. This situation raises legal issues regarding the effectiveness of implementing the rehabilitation model as mandated by laws and regulations. This study aims to analyze the application of the rehabilitation model for drug addicts and assess its suitability for the purposes of punishment and human rights protection. The research method used is normative legal research with a legislative and conceptual approach, through a review of primary, secondary, and tertiary legal materials. The results indicate that rehabilitation has been normatively regulated as the primary mechanism for handling drug addicts, but its implementation still faces obstacles, such as differing interpretations by law enforcement officials and limited rehabilitation facilities. Therefore, policy strengthening and consistent law enforcement are needed so that the rehabilitation model can be optimally implemented.